HealthCare I - Orlando, Valentina; Colonna, Roberto; Coscioni, Enrico; di Gennaro, Massimo; Giordana, Roberta; Guarino, Ilaria; Menditto, Enrica; Mucherino, Sara; Postiglione, Antonio; Riegler, Salvatore; Scafa, Luca; Stefanelli, Roberta; et al. (Pharmàkon, 2022)
One of the main challenges in the healthcare sector in recent years has concerned the effort to ensure the healthcare sustainability in view of demographic change. Due to the progressive increasing of aging and chronic conditions, it is necessary to employ treatment methods with increasingly advanced and costly technological and care requirements that the Italian Health System has to deal with both from a health and economic standpoint. This critical issue also emerged during the COVID-19 pandemic, proving the need to reconsider the management of chronic conditions, which is still too focused on a specialist and/or hospital perspective, to make it more suitable for responding to patients' care issues while respecting available economic resources. In this regard, Outcome Research is of great interest as a research area based on Real World Evidences (RWE). Indeed, analyses of evidence produced in a Real-World context can confirm or not the value of political decision-making to improve governance and the quality of health-services provided. The aim of this work is to provide a detailed snapshot of the prevalence of chronic diseases and related comorbidities in Campania Region. At the same time, it also aims to be an effective knowledge tool for decision-makers involved in the planning of health policies and strategies.